Impact assessment methods toward institutional impact analysis - Ocampo, Romeo B. (2015)
The Philippines has years of experience with the use of various impact assessment (IA) methods, such as environmental impact assessment, traffic impact assessment, and since 2012, the Regulatory Impact Assessment (RIA), which is being promoted by foreign aid agencies. After a review of the development of different IAs, the critical issues that RIA has raised, and Philippine experience with these three forms, this article proposes and outlines what it calls Institutional Impact Assessment (IIA). This article intends to fill the gap in organizational analysis and thereby help in dealing with some of the obstacles in the way of other IA methods. IIA should be useful for both ex ante assessment and ex post evaluation, for proposed and existing measures with significant organizational or institutional implications, including policies, regulations, bills or laws, development projects and government decisions and orders of major consequence.
Keywords: Social impact assessment; Trade regulation; Regulatory impact assessment; Institutional Impact Assessment